Peran Akuntansi Risiko PSAK No. 71 dalam Menjaga Hifz al-Mal pada Bank Syariah : Tinjauan Literatur Kritis dan Konseptual - Misbahussururi, Adila; Azwar, Peny Cahaya (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2025)
This study aims to analyze the role of implementing PSAK No. 71 concerning Financial Instruments in realizing the principle of Hifz al Mal (protecting assets) in Islamic banks. This study uses a critical and conceptual literature review method by analyzing various literature related to PSAK 71, Islamic finance, and Maqashid Syariah. The results show that PSAK No. 71 plays a strategic role in supporting Hifz al Mal through the application of prudential principles such as the recognition of expected credit losses that provide an earlier picture of risk. Conceptually, this standard is aligned with the Islamic principle of protecting assets. However, its implementation faces challenges, such as the potential tension between fair valuation and the concept of value in Islamic contracts, which requires in-depth interpretation to fully align with Islamic business ethics.